Interpretasi Mimpi Melalui Film Pendek Finding A Dream Menggunakan Teknik Animasi Hybrid - Ely Rosita (Institut Seni Indonesia Yogyakarta, 2026)
Interpretation of Dreams through the Short Film “Finding a Dream” Using Hybrid Animation Techniques. This study examines the creation process of the short film Finding a Dream, which uses hybrid animation techniques to interpret dreams. The work is based on the artist's personal experience of trying to understand the emotional connection with her deceased father. Hybrid animation techniques, which combine 2D and 3D animation, were chosen to visually aesthetic and emotionally profound imagery. The creation of this work employed a Research-Based Practice approach in three stages: reflection, experimentation, and formation, with a focus on symbolism and innovative animation techniques. The results of the study indicate that hybrid animation can depict the difference between the real world and the dream world through symbols, such as the use of white lines on the father character, representing an unattainable presence. Furthermore, this study introduces hybrid animation as a potential approach in the Indonesian animation industry, particularly as an alternative to the dominance of 3D animation. It has been proven that 2D animation, through a hybrid approach, remains relevant and keeps producing rich, meaningful narratives. In addition to presenting compelling visuals, this work also explores themes of longing and the search for meaning, thereby strengthening the emotional narrative in the animation medium. The study concludes that hybrid animation techniques can be a significant innovation in the animation industry and offer new ways to explore complex psychological and emotional themes.